Digital twin application in energy storage: Trends and challenges. (February 2023) - Semeraro, Concetta; Olabi, A.G.; Aljaghoub, Haya; Alami, Abdul Hai; Al Radi, Muaz; Dassisti, Michele; Abdelkareem, Mohammad Ali
Abstract: The digitalization of engineering systems has attracted huge attention in the last years due to its wide benefits on the performance and cost of the overall system. Among these digitalization techniques, digital twins emerge as a potential technique for enhancing performance, lowering maintenance and operation costs, and ensuring safer operation for any associated system. The energy storage field is crucial in designing and operating any energy-demanding system, both grid-connected and mobile operating. This work reviews the application of digital twin technology in the field of energy storage while simultaneously assessing the application contexts, lifecycle stages, digital twin functions, and digital twin architecture. This work presents a detailed view of the primary knowledge and features of the current research on digital twins implemented in various functional energy storage systems, including electrochemical energy storage, mechanical energy storage, and thermal energy storage. Finally, this work aims to depict the various application fields of the digital twin and the associated technologies and gives future research directions for pushing this technology closer to practical implementation. Highlights: Review the application of digital twin in energy storage systems Analyze the digital twin application, context, lifecycle, functions, architecture, and components in energy storage Define the main research challenges of digital twin application in energy storage